Apps in Clinical Practice: Usage Behaviour of Trauma Surgeons and Radiologists in Northern Germany - Marie Keitsch; Alonja Reiter; André Strahl; Karl-Heinz Frosch; Josephine Berger-Groch; Matthias Priemel (International Journal of Telemedicine and Applications)
Introduction. Apps, in general, are an integral part of our daily lives. To investigate the current usage behaviour of trauma surgeons and radiologists regarding medical apps in clinical practice and to find out if and how the current range of medical apps can be improved, we surveyed trauma surgeons and radiologists in northern Germany. Material and Methods. An online questionnaire was sent to 100 trauma surgeons and 100 radiologists in northern Germany. Participants were asked about the frequency of their use of medical apps in clinical practice, which apps were used most often, how useful participants thought apps were, and in which area they would like to see improvements. The most frequently mentioned apps were finally analyzed. Results. The survey study showed that 87.4% of the trauma surgeons and 67.4% of the radiologists use medical apps on a regular basis at work. It also revealed that trauma surgeons used medical apps much more often than radiologists and that young doctors were more likely to rely on medical apps than chief physicians. 80.0% of the participants would pay at least 5 euros for a medical app. Trauma surgeons see the greatest need for support in their daily work from medical apps in the area of treatment, while radiologists seek more support in the area of classification. Conclusion. The study underscored the broad acceptance of medical apps in everyday clinical practice. As the physicians are willing to spend money and stated a general interest and need for further developments, there is high potential for the future. This trial is registered with DRKS00026766.